Konstruksi Pendidikan Sosial Keagamaan PSNU Pagar Nusa di Pesantren Sunni Darussalam - Syafi’i, Wahid (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2025)
This study explores the construction of socio-religious education implemented by Pencak Silat Nahdlatul Ulama (PSNU) Pagar Nusa at the Sunni Darussalam Islamic Boarding School in Yogyakarta. Employing a qualitative field research approach, the study focuses on the experiences of santri (students) as the primary subjects. Through direct observation, interviews, and documentation, this research identifies key educational patterns developed within the Pagar Nusa framework. The findings reveal four main forms of educational action: (1) adaptive actions, where PSNU Pagar Nusa adjusts its educational approach to align with the social and cultural environment of the santri; (2) goal-oriented actions, characterized by the internalization of moral and ethical values as part of character formation; (3) integrative actions, aimed at strengthening the collective spirit and religious-social identity of the students; and (4) pattern-maintaining actions, which ensure consistency and sustainability in the transmission of socio-religious teachings. These educational practices reflect a holistic model that integrates martial arts with religious and social values, contributing significantly to the personal and communal development of the students. This study highlights the unique role of PSNU Pagar Nusa not merely as a martial arts organization, but also as a medium of transformative religious-social education in the pesantren environment.